Q:

Given that f(x) = 6x - 5 g(x) = 3x + 4 and h(x) = 4x – 6 2 Find:- i) g(-2) = ii) g[h(x)] = iii) f[g(2)] =iv) gᴏh(2) vi) h-1(11

Accepted Solution

A:
Answer:(i) [tex]g(-2)=-2[/tex](ii) [tex]g[h(x)]=12x-14[/tex](iii) [tex]f[g(2)]=55[/tex] (iv) [tex](g\circ h)(2)=10[/tex](v) [tex]h^{-1}(11)=\frac{17}{4}[/tex]Step-by-step explanation:The given functions are[tex]f(x)=6x-5[/tex][tex]g(x)=3x+4[/tex][tex]h(x)=4x-6[/tex](i) Find g(-2).Substitute x=-2 in g(x).[tex]g(-2)=3(-2)+4\Rightarrow -6+4=-2[/tex](ii) Find g[h(x)][tex]g[h(x)]=g(4x-6)[/tex]                 [tex](h(x)=4x-6)[/tex][tex]g[h(x)]=3(4x-6)+4[/tex]           [tex](g(x)=3x+4)[/tex][tex]g[h(x)]=12x-18+4[/tex][tex]g[h(x)]=12x-14[/tex](iii) Find f[g(2)].[tex]f[g(2)]=f[3(2)+4][/tex]           [tex](g(x)=3x+4)[/tex][tex]f[g(2)]=f(6+4)[/tex][tex]f[g(2)]=f(10)[/tex][tex]f[g(2)]=6(10)-5[/tex]           [tex]f(x)=6x-5[/tex][tex]f[g(2)]=55[/tex] iv) Find gᴏh(2).[tex](g\circ h)(2)=g[h(2)][/tex][tex](g\circ h)(2)=12(2)-14[/tex]           (From part (ii) we get [tex] g[h(x)]=12x-14)[/tex][tex](g\circ h)(2)=10[/tex](v) Find [tex]h^{-1}(11)[/tex]First find [tex]h^{-1}(x)[/tex].[tex]h(x)=4x-6[/tex][tex]y=4x-6[/tex][tex]x=4y-6[/tex][tex]x+6=4y[/tex]Divide both sides by 4.[tex]\frac{x+6}{4}=y[/tex][tex]h^{-1}(x)=\frac{x+6}{4}[/tex]Substitute x=11 in the inverse function.[tex]h^{-1}(11)=\frac{11+6}{4}[/tex][tex]h^{-1}(11)=\frac{17}{4}[/tex]